KOMPARASI SISTEM PEMBUKTIAN DALAM KASUS PERJANJIAN PENETAPAN HARGA DI SEKTOR KEPELABUHANAN ANTARA INDONESIA DAN MALAYSIA: Comparison of Evidentiary Systems of Price-Fixing Agreement in the Sector of Port Services in Indonesia and Malaysia - Dinda Shishilia Sari; N.G.N Renti Maharaini Kerti (Faculty of Law, Universitas Trisakti, 2026)
Ports are a strategic sector in supporting trade and the country's economy, but in practice, they are prone to unhealthy business rivalry, such as price-fixing agreements. The problem formulation examined is how the competition authorities in Indonesia and Malaysia prove alleged violations of price-fixing agreements in the port services sector. The research method used is normative legal research with a comparative law approach, using secondary data from primary legal sources such as laws and related legal literature. The results of the discussion and conclusions of this article show that Indonesia and Malaysia recognize the Per se Illegal and Rule of Reason legal approaches, as well as the use of direct or indirect evidence. However, there are significant differences in the consistency of the application of the legal approach by the Business Competition Supervisory Commission (KPPU) in Indonesia